Enigmatic objects notes towards a history of the museum in the Philippines - Mojares, Resil B. (Ateneo de Manila University Press, 2023)
"In Enigmatic Objects, Resil B. Mojares traces from colonial history the beginnings of museums in the Philippines--from the 'gabinetes' and 'museos' of Spanish colonial-era educational institutions and the private collections of 'ilustrados', to the first attempts at institutionalizing public libraries and museums in the early period of American rule. Through vignettes that take off from such eccentric and eclectic items as the earliest extant portrait of a Filipino, skulls of bandits measured to explain the phrenology of crime, the fabled pestle of an indigenous hero, and teapots made of coconuts, the book itself becomes a cabinet of curiosities where the act of collecting and displaying intertwines with narrating a nascent Filipino nation." --Back cover.